2023
DOI: 10.1111/jocn.16645
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and nurse–patient interaction among NH residents: Loneliness is detrimental, while nurse–patient interaction is fundamental

Abstract: Aims and ObjectivesTo investigate the association between perceived nurse–patient interaction and quality‐of‐life among nursing home residents, adjusted for loneliness, anxiety and depression.BackgroundSymptoms of anxiety and depression are known to residents of nursing homes along with cognitive impairment, physical inactivity and low quality‐of‐life. Anxiety, depression and loneliness are found detrimental to NH residents' quality‐of‐life. The nurse–patient relationship is important for patient's well‐being,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…In this light, the ways in which the staff interact with the residents represent a powerful resource for the alleviation of loneliness and facilitation of meaningfulness. Evidence has shown that how NH residents perceive the nurse-patient interaction significantly impacts their meaning-in-life (Haugan, 2014b), hope (Kuven et al, 2023), self-transcendence (Haugan et al, 2020), sense of coherence (Drageset et al, 2020), loneliness (Jansson et al, 2017;Drageset and Haugan, 2021), joy of life , anxiety and depression (Kuven et al, 2023). To be seen in the eyes of another person is crucial for the existence of a human being and to experience connectedness to the world (on Buber, see Friedman, 2002Friedman, [1955).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this light, the ways in which the staff interact with the residents represent a powerful resource for the alleviation of loneliness and facilitation of meaningfulness. Evidence has shown that how NH residents perceive the nurse-patient interaction significantly impacts their meaning-in-life (Haugan, 2014b), hope (Kuven et al, 2023), self-transcendence (Haugan et al, 2020), sense of coherence (Drageset et al, 2020), loneliness (Jansson et al, 2017;Drageset and Haugan, 2021), joy of life , anxiety and depression (Kuven et al, 2023). To be seen in the eyes of another person is crucial for the existence of a human being and to experience connectedness to the world (on Buber, see Friedman, 2002Friedman, [1955).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nearly one third of the residents of NHs in Finland suffer from loneliness (Jansson et al, 2017). Recent studies have shown that NH residents perceive that nurse-patient interaction significantly influences their sense of meaning-in-life and also loneliness (van Wijngaarden et al, 2015;Drageset and Haugan, 2021), that is, their hope, sense of coherence, joy of life and self-transcendence, as well as depression and anxiety (Haugan, 2021;Kuven et al, 2023). Despite the evidence, existential conversations in NHs are rare (Sundström et al, 2019).…”
Section: Introductionmentioning
confidence: 99%